Understanding the impact of the COVID-19 pandemic and its control measures on women and children: a Zimbabwean case study - Taruvinga, Tinotenda; Chingono, Rudo S.; Tembo, Mandikudza; Olaru, Ioana D.; Masiye, Kenneth; Madanhire, Claudius; Munhenzva, Sharon; Sibanda, Sibusisiwe; Mafuva, Lyton; O’Sullivan, Natasha; Osman, Abdinasir Y.; Deane, Kevin; et al. (Frontiers in Public Health, 2025)
The Coronavirus Disease 2019 (COVID-19) posed significant health policy challenges, particularly for low-income countries, where policymakers faced both direct threats from the virus and social and economic harm owing to lockdown measures. We present a holistic contextualized case study of the direct and indirect impacts on women and children, highlighting disparities across socioeconomic, age, and gender groups. We utilized multiple data sources, including primary and secondary data from 28 in-depth interviews, six focus group discussions, and 40 household interviews, as well as data from government reports, District Health Information Software version 2 (DHIS2), and published research. A conceptual framework was devised to hypothesize causal pathways and guide the analysis of results. The findings indicate that the pandemic not only had direct effects, on morbidity and mortality, but also more severe indirect impacts, including job losses and limited access to healthcare, including maternal and child healthcare services, due to measures put in place to control it, which were exacerbated by well-known but inadequately considered preexisting political and economic challenges. The most severe indirect effects on healthcare services availability and wider livelihoods fell on the poorest segments of society, further widening the age and gender inequalities. Policymakers faced significant challenges in managing the direct and indirect harm of COVID-19, including short- and long-term effects and their unequal distribution across society. We conclude that the indirect effects of COVID-19 were at least as harmful, if not more so, than the direct impacts, especially for women and children. In the future, it is highly recommended to establish specific protocols and guidance for maternal and child health service access, including strategies that reduce barriers to social support.